Application of silicone coating to optimize the process of obtaining cellular spheroids by the hanging drop method - S. Y. Filippova; A. O. Sitkovskaya; S. V. Timofeeva; T. V. Shamova; I. V. Mezhevova; N. V. Gnennaya; I. A. Novikova (Южно-Российский онкологический журнал, 2022)
Purpose of the study. To study the effect of SIEL 159–330 coating on the cell clusters formation rate in a hanging drop method in combination with the use of methylcellulose (MC) and collagen as cell aggregation improving agents.Materials and methods. BT20 breast cancer cells were cultured in drops of 20 μL (104  cells per drop) on the lid of a polystyrene Petri dish coated with SIEL 159–330 silicone elastomer (GNIIKHTEOS, Moscow, Russia) or without coating. The study tested three concentrations of MC (0.1 %, 0.25 % and 0.4 %) and collagen (150 µg/ml, 300 µg/ml and 600 µg/ml). The rate of formation of cell conglomerates was assessed by evaluating their area after 4, 24, 48, and 72 hours of cultivation.Results. The use of SIEL 159–330 coating made it possible to obtain spheroids of the same size as the addition of 0.4 % MC over a time interval of 72 hours. The silicone coating additionally reduced the size of cell spheroids in the medium with 0.1 % MC at all time points; however, this effect disappeared with increasing concentration of MC. In addition, the use of SIEL 159–330 reduced the relationship between the size of cellular spheroids and the concentration of MC, which allows us to consider the use of this coating as an alternative to MC or a way to reduce its concentration. In the experiment with the addition of collagen to the culture medium, the sizes of cell conglomerates formed on the silicone coating were significantly smaller than on uncoated plastic in all variants of the experiment and time points. The effect was more pronounced for a collagen concentration of 600 μg/ml. The use of SIEL 159–330 coating, in addition, reduced the variability in the size and shape of the resulting cell conglomerates.Conclusion. Accelerated aggregation of cells and fibers of the extracellular matrix in hanging drops, as well as a reduction in the variability in the size and shape of the resulting cell clusters on SIEL 159–330, allows us to reduce the time of experiments and material costs, as in experiments with the addition of substances that accelerate the formation of spheroids (MC and collagen), as well as in their absence.